Dinâmica de cianobactérias e a detecção molecular de genes produtores de cianotoxinas na Represa Billings - Ribeiro, Matheus Santos Freitas [UNIFESP] (2018)
Billings Reservoir, located in the São Paulo Metropolitan Region, that supplies the cities of Santo André, São Bernardo do Campo, Diadema, Ribeirão Pires and São Paulo, is currently in a eutrophic state that contributes to the cyanobacteria blooms, which in addition to altering the physical and chemical characteristics of water (light penetration, decrease in oxygen levels, etc.) have the capacity to produce toxins, specifically called cyanotoxins. In this work, the potential toxigenic capacity of four different cyanotoxins (anatoxin-a, cylindrospermopsin, microcystin and saxitoxins) in the natural population was studied. These toxins can cause a number of health problems for the biota, including the human population. Therefore, in order for the water of the reservoir to be used for public supply, a series of parameters like monitoring the presence of cyanobacteria and cyanotoxins must be respected. This work is aimed to identify and quantify the occurrence of cyanobacteria in the Central Body 1 of the Billings Reservoir and the presence of genes responsible for the production of four types of cyanotoxins in the natural population of cyanobacteria. Four distinct points were selected at the Billings Reservoir, where four sample collections were carried out in three consecutive years, during different periods of the year (dry and rainy). The presence of the cyanobacteria was evaluated by identification and subsequent quantification by counting and the densities were expressed using biovolume (mm³ / L). The environmental samples were used directly for total DNA extraction and subsequent PCR reactions to detect cyanotoxin producing genes (anatoxin-a - anaC and anaF; cylindrospermopsin - cyrA, cyrB, cyrC and cyrJ; microcystin - mcyE and saxitoxin - sxtA, sxtB and sxtI). The results showed that the cyanobacteria dominated during the drought period and partially during the 4th sample collection (rainy season), reaching the maximum value of 61.65 mm³ / L in point 4 and the lowest value during the 4th sample collection, in point 3 (1.37 mm 3 / L). This dominance of cyanobacteria is mainly related to the environmental variables: precipitation, temperature and solar radiation (correlation matrix). In addition, we can highlight the species Woronichinia naegeliana and Microcystis aeruginosa as dominant species (the first, in all points during the samples carried out on dry season (1 and 3) and the latter on point 2 during the 4th sampling). The results obtained by molecular biology showed the presence of the microcystin-producing genes in the total DNA of the microbial community in all samples studied on this work. As for the other cyanotoxins, the genes related to cylindrospermopsin production were present in the samples obtained on the first and fourth collection and the saxitoxin ones were present only on the first collection. There were no positive amplifications to both anatoxin-a genes studied on this work.